PEMBERDAYAAN MASYARAKAT SEKTOR PARIWISATA BUDAYA DI KOTA CIMAHI - Cecep Ucu Rakhman (Universitas Merdeka Malang, 2019)
This research is a tourism culture study that aims to find out how community empowerment in the cultural tourism sector in the City of Cimahi is seen based on five dimensions of empowerment, namely enabling, strengthening, supporting, protecting, and foresting. The research method used is qualitative with data collection techniques using in-depth interviews, observation, documentation studies, and triangulation techniques. The emic analysis model and the analytical method are descriptive. From the results of research in the field it is known that community empowerment in the cultural tourism sector has been able to provide many benefits to the community in Cimahi City. In addition, community empowerment in the cultural tourism sector in the city of Cimahi that is studied based on the dimensions of enabling, strengthening, supporting, and protecting has also been going well. Only in a foresting dimension that has not been good. This is because community empowerment in the cultural tourism sector has not been based on strong commitment from all stakeholders.